Pengaruh Mental Toughness dan Cultural Intelligence yang di Mediasi oleh Organizational Commitment terhadap Learning Goal Orientation pada Pegawai yang Bekerja secara Shifting di Pabrik - Irsaputri, Zahira Rabinawal; Emilisa, Netania (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2024)
This research aims to analyze mental toughness, cultural intelligence, organizational commitment, and learning goal orientation in shift workers at the Toyota Karawang factory. The method is quantitative with hypothesis testing, treating mental toughness and cultural intelligence as independent variables, organizational commitment as a connecting variable, and learning goal orientation as the dependent variable. Data was collected through a questionnaire with purposive sampling among Toyota Karawang workers. Minimum sample of 155 respondents. This research has the potential to contribute to the understanding of variable relationships in the Toyota Karawang factory work environment. The results of hypothesis testing show that Mental Toughness has a significant positive impact on Learning Goal Orientation, while Cultural Intelligence has a significant negative impact, and Organizational Commitment has a significant positive impact. However, Mental Toughness does not have a significant impact on Organizational Performance. Cultural Intelligence also has a significant negative impact on Organizational Commitment. Furthermore, no significant impact was found between Mental Toughness or Cultural Intelligence on Learning Goal Orientation which was mediated by Organizational Commitment. A study of shift workers at Toyota Karawang found that the average score for Mental Toughness, Cultural Intelligence, Organizational Commitment, and Learning Goal Orientation was around